2018
DOI: 10.1155/2018/4530849
|View full text |Cite
|
Sign up to set email alerts
|

UPLC‐QTOF/MS‐Based Lipidomic Profiling of Liver Qi‐Stagnation and Spleen‐Deficiency Syndrome in Patients with Hyperlipidemia

Abstract: Hyperlipidemia is a common disease caused by abnormal plasma lipid metabolism. Lipidomics is a powerful and efficient technology to study the integration of disease and syndrome of Chinese medicine. This study investigated specific changes in lipid metabolites from hyperlipidemia patients with syndrome of liver qi-stagnation and spleen-deficiency (SLQSD). Lipid profiles in plasma samples from 29 hyperlipidemia patients including 10 SLQSD and 19 non-SLQSD and 26 healthy volunteers (NC) were tested by UPLC-QTOF/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Hyperlipidemia is a common disease caused by abnormal blood lipid metabolism, which is considered to be a highly independent risk factor for atherosclerotic cardiovascular and cerebrovascular diseases, such as CHD and stroke (Shenghua et al, 2018). Hyperlipidemia is the result of complex interactions between genetic and environmental factors, which can be treated by altering the diet and drugs that regulate lipid metabolism through many mechanisms (Chu et al, 2015).…”
Section: S Miltiorrhiza For the Treatment Of Clinical Cardiovascularmentioning
confidence: 99%
“…Hyperlipidemia is a common disease caused by abnormal blood lipid metabolism, which is considered to be a highly independent risk factor for atherosclerotic cardiovascular and cerebrovascular diseases, such as CHD and stroke (Shenghua et al, 2018). Hyperlipidemia is the result of complex interactions between genetic and environmental factors, which can be treated by altering the diet and drugs that regulate lipid metabolism through many mechanisms (Chu et al, 2015).…”
Section: S Miltiorrhiza For the Treatment Of Clinical Cardiovascularmentioning
confidence: 99%
“…Qi deficiency could affect energy metabolism and blood stasis in human, and Qi defciency is the main syndrome of hyperlipidemia ( Piao, Guo, & Hu, 2012 ). The study of some researchers showed that there were obvious abnormal differences in lipid metabolism in patients with Qi deficiency, including TC, TG, LDL-C and so on ( Shenghua et al, 2018 ). KP has been extensively performed to supplement Qi and calm the mind in patients, which could enhance metabolism and regulate lipid metabolism ( Dong et al, 2020 , Wang et al, 2020b , Zhou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics, which focuses on endogenous small-molecule metabolites within the organism and investigates the comprehensive dynamic patterns of their types and quantity changes, aligns with the holistic perspective of TCM theory and has been widely applied in the TCM field for the discovery of disease biomarkers, evaluation of pharmacological effects and toxicity, and exploration of mechanisms of action [ 22 , 23 ]. In consideration of this, the present study utilizes a combination of factors (CRS and adenosine) to establish a rat model of infertility, conducting a comprehensive evaluation encompassing ethological analysis, biochemical indices, organ coefficients, and histopathology to assess the established model’s alignment with clinical features of MI with LD & KD in both TCM and modern medicine.…”
Section: Introductionmentioning
confidence: 99%